2012
DOI: 10.1093/intimm/dxs081
|View full text |Cite
|
Sign up to set email alerts
|

Extended cleavage specificity of the mast cell chymase from the crab-eating macaque (Macaca fascicularis): an interesting animal model for the analysis of the function of the human mast cell chymase

Abstract: Serine proteases are the major protein constituents within mast cell secretory granules. These proteases are subdivided into chymases and tryptases depending on their primary cleavage specificity. Here, we present the extended cleavage specificity of the macaque mast cell chymase and compare the specificity with human chymase (HC) and dog chymase (DC) that were produced in the same insect cell expression host. The macaque chymase (MC) shows almost identical characteristics as the HC, including both primary and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 52 publications
0
27
1
Order By: Relevance
“…In addition, macaques have only one chymase in their chymase locus. For these reasons, with the exception of the ethical concerns, macaques seem to be an excellent animal model to study the biology of HC (37). In addition and interestingly, the almost complete absence of cleavage of any of the chemokines analyzed in this study indicates that these two enzymes have no or a lesser role in controlling chemokine activity in vivo.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In addition, macaques have only one chymase in their chymase locus. For these reasons, with the exception of the ethical concerns, macaques seem to be an excellent animal model to study the biology of HC (37). In addition and interestingly, the almost complete absence of cleavage of any of the chemokines analyzed in this study indicates that these two enzymes have no or a lesser role in controlling chemokine activity in vivo.…”
Section: Discussionmentioning
confidence: 65%
“…Of the noncytokine chemokine targets identified for these enzymes, some are relatively well conserved, whereas others are cleaved only in primates (e.g., cleavage of secretory leukocyte protease inhibitor, which is cleaved by HC and macaque chymase but not by dog chymase) (37). In contrast, fibronectin and angiotensin I seem to be common targets for the chymases of many mammals (37). Recently, it also was shown that mMCP-4 degrades IGF-1, leading to adverse effects in cardiac remodeling after infarction (25).…”
Section: Discussionmentioning
confidence: 99%
“…Since, chymase is kept in control by AAT [21], it is quite possible that overexpression of chymase triggers the up-regulation of AAT in VKC patients. Chymase converts angiotensin-I to angiotensin-II [22] and also activates some endogenous peptides like endothelin, stem cell factor and interleukin-1β (IL-1β) [23], IL-1, IL-6, TNF-α and lipopolysaccharides have shown to up-regulate the synthesis of AAT [24]. IL-1 may therefore account for the increased antitryptic activity in the serum of VKC patients.…”
Section: Discussionmentioning
confidence: 99%
“…As neither chromogenic substrates nor phage display resulted in any information concerning the extended specificities of these three platypus enzymes, we instead tried a third alternative; to use a new type of recombinant substrate. A panel of such substrates has previously been designed and produced for the verification of the extended cleavage specificity following phage display analysis for a number of previously analysed mammalian hematopoietic and coagulation serine proteases [17,[21][22][23][24][25][26][27][28][29][30].…”
Section: Analysis Of the Extended Cleavage Specificity By The Use Of mentioning
confidence: 99%